PENGGUNANAAN MEDIA PERMAINAN SNAKES AND LADDERS UNTUK MENINGKATKAN KEMAMPUAN MAHAROH KALAM - Muhammad Mujabun; Amrini Shofiyani (Al-Lahjah, 2019)
The use of snakes and ladders game on the material أمال المراهقين (the ideals of the youth) is very feasible as a medium of learning Arabic according to media and material experts, as well as Arabic Language Teachers. The application of snake ladder learning media on the آمال المراهقين material (the ideals of teenagers) is effective in the activities and learning outcomes of students. In addition, the students' response analysis of the learning medium of the Arabic snake ladder game has a positive effect, because learning Arabic becomes more active, innovative, creative and effective. The use of this game media requires Arabic teachers to conduct an explanation for all their students to read and understand the instructions for using the snakes and ladders game as a learning medium so that the learning process can take place smoothly and there are no students who do not understand the technical playing. The teacher is also obliged to prepare well time management, the application of snake ladder media with this material آمال المراهقين (the ideals of the youth), so that learning is completed on time and all question cards can be resolved. The use of snakes and ladders game learning media is recommended to be developed for other materials with variations of questions in accordance with the development of existing knowledge. Keywords: Learning Media, Snakes and Ladders Game, Maharoh Kalam